Pemberdayaan masyarakat desa pulau harapan melalui inovasi produk Kemplang Tunu sebagai alternatif usaha kreatif - Anjani, Shevanova Putri; Azfa, Naila Siti; Diinah, Chelsea Luthfia (Nur Science Institute, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy, contributing more than 60% to GDP and accounting for 97% of the workforce. However, culinary MSMEs in Palembang still face challenges, including a lack of product innovation, ineffective marketing strategies, and unattractive packaging. This community service program aims to empower the people of Pulau Harapan Village through the product innovation of kemplang tunu as a creative business alternative, using a participatory, innovative approach comprising several stages: initial observation, product design, digital promotion and training, packaging innovation, and evaluation and monitoring. The program introduces an innovative kemplang product served with cuko, a traditional Palembang sauce, to the local PKK women's group, while providing training in digital marketing through platforms such as Facebook Pro, TikTok Shop, and WhatsApp Business, and educating participants on creating attractive, hygienic packaging. The results show increased community knowledge of product innovation, improved skills in digital marketing and modern packaging techniques, and a stronger entrepreneurial spirit among PKK women, who can also continue their primary occupation as rubber farmers.